Sleep quality and cardiorespiratory endurance in adolescent competitive swimmers - Muhammad Arpan Syaipul; Eval Edmizal; Yendrizal Yendrizal; Anisa Sholiha Mia (Journal of Educational and Learning Studies, 2026)
Being able to last through a race is largely determined through training and endurance ability in swimming. Sleep is also a way to improve recovery and thus is regarded as a way to modify recovery and support adaptation to cardiorespiratory activities of young athletes by experts. Not many studies have looked at this relationship between sleep quality and sport performance in adolescent swimmers from clubs compared to that of elite swimmers or college players. Through this study, we wanted to establish whether or not sleep and cardio capacity can go hand in hand with our teenage swimmers from Ladies Swimming Club. We applied a numerical correlational model to the situation and a complete sampling of the population as only 10 swimmers were on the register (ages 13 to 17, mean age was 14.8 and SD was ±1.48). The instrument employed to evaluate sleep quality of athletes during the study was the Pittsburgh Sleepiness Scale (PSQI) and VO₂max was calculated from the Multistage Fitness Test (Bleep Test) using Ramsbottom formula. Analysis of the data included the Shapiro-Wilk test of normality and then the Pearson correlation if there was no departure from normal distribution. Findings: The PSQI range was 2 to 13 (M = 6.30, SD = 3.09); 60% of swimmers were considered as having a good sleeping habit while the remaining 40% slept not too well. The estimated VO₂max values varied from 33.32 to 53.50 ml/kg/min (M = 44.54; SD = 7.51). Both PSQI and VO₂max measures were within the normal distribution (PSQI: W = 0.909, p = 0.271; VO₂max: W = 0.876, p = 0.118). The result shows that there was a strong and negative relationship between PSQI and VO₂max with a significant statistical level (r = -0.910, p = 0.00025), meaning that sleep quality was the major reason behind such variations in endurance (R² = 0.8288). Our findings demonstrated that sleep quality is linked with cardiorespiratory endurance. Lower quality sleep was associated with lower endurance. Areas of use: It would be beneficial for coaches and other professionals involved in athletes' development or training to include the monitoring of athletes' night time sleep and provide education on sleeping habits into their daily routines, since they are responsible for a large part of the training plan and hence of the athletes' period and recovery as well.